Analisa Pengaruh Modifikasi Mesin Press Body Area 5a Line Terhadap Peningkatan Kapasitas Produksi Di PT. Astra Daihatsu Motor - Januar Nasution; Wisnu Adi Putranto (Bina Nusantara University, 2011)
Analysis or the analysis is defined as a study conducted on a discussion of the problems studied in depth to find out the real situation. In this study, analysis of the modifications carried out to assess the influence of such modifications in an increase in production capacity of PT. Astra Daihatsu Motor. Taking into account the physical and technical aspects of data in the field, didapatlah data supporting this research, for subsequent use as a reference from the financial aspect to determine the magnitude of the cost involved in this modification. The purpose of this study was to find the value of the initial investment required in the modification, finding the investment payback period, benefit gained as well as determining whether modification is appropriate or not to apply. Data collection conducted broadly divided into two data technical and financial aspects, and then after that the data is processed through the method of calculation of production, Stoke per Hour (SPH), Gross Stroke per Hour (GSPH). This study also provides recommendations to companies to assess whether the modification is feasible or not to do, from the point of view of project feasibility studies.